Analisis Perkembangan Masa Bayi - Violla Wulandari; Padilatul Ilmi; Linda Yarni (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The research aims to analyze the understanding of emotional development in babies, how cognitive development in babies is, what the risks or dangers are to babies, and what are the implications of infancy development in counseling services. The research method used in this research is library research. It is a search and research of literature by reading and reviewing various journals. Data collection techniques use library research in the form of books, journals and other studies. The data analysis technique uses descriptive analysis. The results of the research show that babies' emotions are very susceptible to habituation, there are several differences in this pattern and also in the stimuli that cause it. development of understanding. Infant perception through sensory explanations. Like babies looking, feeling, smelling, and painting all objects within their reach. Maturation during infancy usually occurs through direct experience with the environment and interaction with objects and people around them. Dangers during infancy can be physical dangers and psychological dangers. Physical dangers such as excessive crying, it could also be a baby suffering from brain damage or other birth defects. And psychological dangers such as emotional dangers, this usually occurs because a lack of love from parents towards the baby can give rise to unstable emotions in the baby. The implication of development during infancy in counseling services is to ensure the baby's development and provide services according to the baby's condition.